Self-Confidence and Badminton Athlete Performance: A Bibliometric Analysis - Kevin Naufal Dirgantara; Burhan Hambali; Yusuf Hidayat; Agus Gumilar (Universitas Negeri Semarang, 2026)
Self-confidence influences badminton performance via pathways that alleviate anxiety, enhance focus and maintain tactical execution, but global reviews of these pathways are fragmented. The objective of this study is to map the global research landscape on self-confidence and badminton athlete performance, quantify the productivity and collaboration patterns, and identify the thematic gaps. We analyzed 4,550 open-access English-language articles indexed in Scopus (2022-2026; export date April 22, 2026) using a three-level reduction strategy: the full sport and sport psychology field (n = 4,550), a sport psychology subset (n = 894), and a badminton subset (n = 26), with a core subset of 20 articles linking badminton to psychological constructs. Performance and science-mapping analyses were performed using Python (pandas, matplotlib, seaborn) and Biblioshiny. Total publications increased by 205% from 2022 (n = 467) to 2025 (n = 1,423). The subset of sport psychology tripled (88 to 275). The most prolific journal was Frontiers in Psychology with 96 articles. The United States (141), United Kingdom (129) and China (108) led the sport psychology output while Indonesia contributed 42.3% of badminton articles (11 of 26). The most common author keywords were self-efficacy (47), self-confidence (35), and performance (35). There are only 20 core articles worldwide about badminton and psychological constructs. Self-confidence is a key, yet less explored, construct in badminton research. Badminton-specific output is dominated by Indonesia, but longitudinal, gender-sensitive and intervention studies are urgently needed.